1996
DOI: 10.1104/pp.110.4.1097
|View full text |Cite
|
Sign up to set email alerts
|

The Competence of Maize Shoot Meristems for Integrative Transformation and Inherited Expression of Transgenes

Abstract: We have developed a nove1 and reproducible system for recovery of fertile transgenic maize (Zea mays L.) plants. The transformation was performed using microprojectile bombardment of cultured shoot apices of maize with a plasmid carrying two linked genes, the Strepfomyces bygroscopicus phosphinothricin acetyltransferase gene (bar) and the potato proteinase inhibitor II gene, either alone or in combination with another plasmid containing the 5' region of the rice actin 1 gene fused to the Escbericbia coli p-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…However, to date, the closest researchers have come to directly using mature seed tissues for transformation in monocots has been a report in which a brief preculture period (1 to 5 d) was used before Agrobacterium-mediated DNA delivery in japonica rice (Toki et al, 2006). The remaining reports of "mature seed transformation" in monocots have all progressed through an intermediate culture step, using either embryogenic callus (Hiei et al, 1997;Chen et al, 1998;Dai et al, 2001;Sidorov et al, 2006;Ahmadabadi et al, 2007), organogenic callus (O' Connor-Sánchez et al, 2002) or proliferating meristem cultures (Zhong et al, 1996;Zhang et al, 2002), and finally using the proliferating cultured cells as the transformation target. Here, using the transcription factors Bbm and Wus2, we demonstrated that cells in the exposed embryo axis of mature maize seed can reproducibly produce transgenic callus and regenerate healthy, fertile T0 plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, the closest researchers have come to directly using mature seed tissues for transformation in monocots has been a report in which a brief preculture period (1 to 5 d) was used before Agrobacterium-mediated DNA delivery in japonica rice (Toki et al, 2006). The remaining reports of "mature seed transformation" in monocots have all progressed through an intermediate culture step, using either embryogenic callus (Hiei et al, 1997;Chen et al, 1998;Dai et al, 2001;Sidorov et al, 2006;Ahmadabadi et al, 2007), organogenic callus (O' Connor-Sánchez et al, 2002) or proliferating meristem cultures (Zhong et al, 1996;Zhang et al, 2002), and finally using the proliferating cultured cells as the transformation target. Here, using the transcription factors Bbm and Wus2, we demonstrated that cells in the exposed embryo axis of mature maize seed can reproducibly produce transgenic callus and regenerate healthy, fertile T0 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Among reports of successful transformation of callus, the explants from which the callus was first derived include (1) immature tassels, immature ears, or anthers in maize (Cheng et al, 2004); (2) leaf bases from maize (Sidorov et al, 2006;Ahmadabadi et al, 2007); and (3) scutellum from mature seeds in rice (Chen et al, 1998;Dai et al, 2001). Alternatively, explants used to initiate proliferating meristem cultures for subsequent transformation have included maize apical or nodal meristems (Zhong et al, 1996;Zhang et al, 2002) or mature seeds in species such as rice (Cho et al, 2004), oat (Avena sativa; Cho et al, 1999), orchardgrass (Dactylis glomerata; Cho et al, 2000a), Kentucky bluegrass (Poa pratensis; Ha et al, 2000), and fescue (Festuca sp; Cho et al, 2000b). Regardless of the culture type, all of these reports have relied on the manipulation of exogenous hormones in the culture media to produce either embryogenic callus or multiple meristems for use as the transformation target.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were immersed in GUS substrate mixture and incubated at 37°C as described elsewhere (Jafferson et al 1987). Tissues were prepared using free-hand cross sections and were examined under a Zeiss SV8 stereomicroscope according to Zhong et al (1996).…”
Section: Histochemical Analysis Of Gusmentioning
confidence: 99%
“…By using above optimized parameters an average transformation frequency of 3.25% was achieved. Comparatively, explants derived from the mature embryos (Cao et al, 2014;Huang and Wei, 2005;Zhong et al, 1996) yielded less frequencies of transformation than the immature embryos (Ishida et al, 1996). All these conditions of different parameters would help us in developing a congenial high throughput method of Agrobacterium mediated genetic transformation in maize.…”
Section: Recovery Of Fertile Transgenic Plants Throughmentioning
confidence: 99%